Active surveillance of adverse events following coronavirus disease 2019 immunization in the elderly population: A prospective multi-centric study from Jaipur, Rajasthan, India - Surya Pratap Singh Tiwari; Bhandari Anil; Rathore Monika; Sharma Lokendra; Sharma Aditya; Jain Smita; Agarwal Madhav (Journal of the Indian Academy of Geriatrics, 2021)
Background: Vaccine against coronavirus disease 2019 (COVID-19) was rolled out in India to prevent the infection caused by severe acute respiratory syndrome coronavirus 2. We aimed at investigating the adverse events following immunization (AEFI) associated with the first dose of Covishield (ChAdOx1 nCoV-19) vaccine in the elderly population (60 and above). Methodology: An observational study, conducted among 463 vaccinated individuals at multiple community health centers in Jaipur, of AEFIs associated with the first dose of Covishield vaccine. We investigated these AEFIs through telephonic interviews, using pharmacovigilance per forma provided from the Indian Pharmacopoeia Commission, Ghaziabad. Results: Four hundred and sixty-three people responded to the telephone survey. About 7.7% (36/463) of the respondents experienced AEFIs. Of these, commonly reported systemic AEFI were fever (47.2%), fatigue (38.8%), dizziness (5.5%), and diarrhea (2.7%), and local AEFI were injection site soreness (27.7%) and itching with rash (2.7%) AEFI reported in the age group (60–70) was higher (8.7%, 26/297) than those above 70 (6.2%, 10/166). Females (9.9%, 20/202) were associated with higher AEFI than males (6.1%, 16/261). More than one-third (43.8%, 203/463, P = 0.001) were hesitant before vaccination. Respondents in the age group of 60–70 years (55.2%, 164/297) were more hesitant than those above 70 (23.4%, 39/166). There is no association between gender and AEFI status and age group and respondent's AEFI. Conclusion: Only 7.7% of the respondents experienced AEFIs associated with ChAdOx1 nCoV-19, though all were mild and self-limiting. There were no serious events requiring hospitalization, and most AEFIs improved within few days. Vaccine hesitancy among 43.8% of the respondents could be attributed to the unscientific information on social media.